Prevalence and localization of Canalis Sinuosus: a mini review - Angiolani, Francesca; Piattelli, Maurizio; Rinaldi, Fabiola; Trubiani, Oriana; Varvara, Giuseppe (Italian Journal of Anatomy and Embryology, 2023)
In recent years, scientific literature has been focusing on the study of the Canalis Sinuosus (CS); this canal contains the anterior superior alveolar nerve (ASAN), together with bundles. Accordingly, the CS may vary its frequency and anatomical features. These variations can be identified through imaging technologies such as cone beam computed tomography (CBCT). The aim of this mini review is to present the current understanding of the CS, its prevalence and localization in order to decrease the potential surgical risk associated with this region. As revealed by the analysis of the international literature available, presence of CS is a crucial factor to consider in implantology and generally in oral surgery procedures in this area. In conclusions the use and analysis of CBCT imaging in the diagnosis stage is fundamental to preserve the most important anatomical structures which are present in the jaws.